Diagnostic yield of conventional transbronchial needle aspiration in suspected bronchogenic carcinoma without intraluminal growth on bronchoscopy - Rennis, Davis Kizhakkepeedika; Krishnakumar, Easwaramangalath Venugopal; Sankarapotti, Navmi (International Journal of Research in Medical Sciences, 2017)
Background: Bronchogenic carcinoma with spread along the mucosal plane presents as an exophytic mass. Most of the submucosal and peribronchial patterns of this malignancy are harder to detect by standard diagnostic procedures such as bronchial washing, brushing and forceps biopsy. We sought to investigate the utility of transbronchial needle aspiration (TBNA) in the diagnosis of bronchogenic carcinoma without intraluminal mass, through prospective analysis of routine diagnostic bronchoscopies performed in a 24-month period, at a tertiary care hospital. Methods: Patients with suspected bronchogenic carcinoma (clinical and radiological) underwent standard computed tomography (CT) of thorax. Further the patients were subjected to conventional TBNA, singly, and in combination with bronchial washings and brushings. The results were analyzed statistically for the diagnostic yield of TBNA. Results: Among the 42 patients assessed, 29 had malignancy confirmed by forceps biopsy or CT guided Fine Needle aspiration cytology or biopsy and bronchoscopy. Among them, 17 cases were detected by a combination of the results of bronchial washing, brushing and TBNA. The individual sensitivities amounted to 3.4% (n=1), 51.72% (n=15) and 27.6% (n=8), respectively. There were no false positive results. Concerning different bronchoscopic sampling techniques, 9 cases were diagnosed solely by bronchial brushings and 2 cases by TBNA alone. No periprocedural complications were encountered. Conclusions: Value of bronchial brushing in the diagnosis of bronchogenic carcinoma without bronchoscopically visible intraluminal mass is above that of conventional TBNA. Addition of bronchial washings, to bronchial brushings and TBNA has an insignificant impact on the diagnosis.